2020
DOI: 10.5897/ijlp2019.0628
|View full text |Cite
|
Sign up to set email alerts
|

Immune response following Newcastle disease immunization and growth performance of kuroiler, broiler and local Tanzanian chickens

Abstract: Chicken is a major livestock species raised by smallholder households in rural areas in developing countries of Sub-Saharan Africa as a chief source of meat protein and income generation. However, Newcastle disease largely compromises the production of this precious bird under backyard production settings. The purpose of the study was to assess antibody responses and growth performance following Newcastle disease vaccination in kuroiler, broiler, and local Tanzanian chickens raised under the same tropical envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(23 reference statements)
0
1
1
Order By: Relevance
“…The high immune response to Newcastle disease vaccines recorded in normal feathered high and frizzle feathered high chicks in this study differs from the findings of Pitcovski et al 14 , who observed high antibody response in naked-neck chicks. The antibody titre mean values recorded at 21 days post-inoculation (PI) in this study were higher than the observed values recorded by Mpenda et al 15 . Sex had significant effects on the immune response to Newcastle disease on chicks of all ages in this study.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The high immune response to Newcastle disease vaccines recorded in normal feathered high and frizzle feathered high chicks in this study differs from the findings of Pitcovski et al 14 , who observed high antibody response in naked-neck chicks. The antibody titre mean values recorded at 21 days post-inoculation (PI) in this study were higher than the observed values recorded by Mpenda et al 15 . Sex had significant effects on the immune response to Newcastle disease on chicks of all ages in this study.…”
Section: Discussioncontrasting
confidence: 89%
“…Female chicks had a higher value than the male counterparts in this study, these as a result of sexual dimorphism in immune response in the animal, where females produce more vigorous humoral immune reactions, which are more resistant to certain infectious diseases. Antibody response to the same virus was different among chicken genotypes study according to Mpenda et al 15 . The selection of chicken genotypes with high protective antibody titres may have a significant contribution in preventing Newcastle disease outbreaks in chicken populations 16 .…”
Section: Discussionmentioning
confidence: 99%